Synthesis and Fungicidal Activities of Some 4-Aryl-1-aroyl-5-cyano-3-methyl pyrazolo [4,5-b], 3,4,7-trihydropyridin-6-ones Derivatives - Tripathi, Praveen; Asthana, R.K.; Ojha, G.S. (Asian Journal of Chemistry, 2010)
A series of 4-aryl-1-aroyl-5-cyano-3-methyl pyrazolo [4,5-b], 4,5,7-trihydropyridin-6-ones have been prepared. The structures of compounds were confirmed by spectral data. Ten compounds were screened for their antifungal activity against two fungi Rhizactonia solani and penicillium citrinum and were found to be fungicidal.